-3m+4=-2m-5

Simple and best practice solution for -3m+4=-2m-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3m+4=-2m-5 equation:


Simplifying
-3m + 4 = -2m + -5

Reorder the terms:
4 + -3m = -2m + -5

Reorder the terms:
4 + -3m = -5 + -2m

Solving
4 + -3m = -5 + -2m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '2m' to each side of the equation.
4 + -3m + 2m = -5 + -2m + 2m

Combine like terms: -3m + 2m = -1m
4 + -1m = -5 + -2m + 2m

Combine like terms: -2m + 2m = 0
4 + -1m = -5 + 0
4 + -1m = -5

Add '-4' to each side of the equation.
4 + -4 + -1m = -5 + -4

Combine like terms: 4 + -4 = 0
0 + -1m = -5 + -4
-1m = -5 + -4

Combine like terms: -5 + -4 = -9
-1m = -9

Divide each side by '-1'.
m = 9

Simplifying
m = 9

See similar equations:

| 12=10y-8y | | x-7=3(x-4) | | 6-x=3(x+10) | | 10b+8b=360 | | 3075=37.5a | | 6x^2+36x+192=0 | | 5x-12=9x+5 | | 3(x+2)+1=2x-8+x+13 | | -16=2a-6a | | 637=13a | | x^2=-2+15 | | 5z=1.7+4.3 | | f(x)=6x^2+36x+192 | | x+37=129 | | 4+(m/5)=6 | | -5n-8-56m=-8 | | 4x^2+9=2x^2+3(5x+3) | | (2x^2)-(1x)-24=0 | | 12h^2-31h+20= | | 3(2x-5)=18 | | x^6+7x^3+64=0 | | 6x=6x-9 | | 3(m+3)-16= | | 36=13w-4w | | X+2=289 | | 10x=-4x+-7 | | -mn+7mp+10m=-2n-8 | | 3a^2+9a+30=0 | | 32=7k-3 | | 4n-6=2n-2n+2 | | X^2-10x-263=0 | | -(1+b)=-(3b-3) |

Equations solver categories